A blinded determination of H0 from low-redshift Type Ia supernovae, calibrated by Cepheid variables. Issue 2 (26th June 2017) - Zhang, Bonnie R.; Childress, Michael J.; Davis, Tamara M.; Karpenka, Natallia V.; Lidman, Chris; Schmidt, Brian P.; Smith, Mathew
Abstract: Presently, a >3σ tension exists between values of the Hubble constant H 0 derived from analysis of fluctuations in the cosmic microwave background by Planck, and local measurements of the expansion using calibrators of Type Ia supernovae (SNe Ia). We perform a blinded re-analysis of Riess et al. (2011) to measure H 0 from low-redshift SNe Ia, calibrated by Cepheid variables and geometric distances including to NGC 4258. This paper is a demonstration of techniques to be applied to the Riess et al. (2016) data. Our end-to-end analysis starts from available Harvard -Smithsonian Center for Astrophysics (CfA3) and Lick Observatory Supernova Search (LOSS) photometries, providing an independent validation of Riess et al. (2011). We obscure the value of H 0 throughout our analysis and the first stage of the referee process, because calibration of SNe Ia requires a series of often subtle choices, and the potential for results to be affected by human bias is significant. Our analysis departs from that of Riess et al. (2011) by incorporating the covariance matrix method adopted in Supernova Legacy Survey and Joint Lightcurve Analysis to quantify SN Ia systematics, and by including a simultaneous fit of all SN Ia and Cepheid data. We find H_0 = 72.5 ± 3.1 (stat) ± 0.77 (sys) km s −1 Mpc −1 with a three-galaxy (NGC 4258+LMC+MW) anchor. The relative uncertainties are 4.3 per cent statistical, 1.1 per cent systematic, and 4.4 per cent total, larger than in Riess et al. (2011) (3.3 per cent total) and the Efstathiou (2014) re-analysis (3.4 per cent total). Our error budget for H 0 is dominated by statistical errors due to the small size of the SN sample, whilst the systematic contribution is dominated by variation in the Cepheid fits, and for the SNe Ia, uncertainties in the host galaxy mass dependence and Malmquist bias.